From Rough Mereology to Robust Navigation: Expanding Mobile Robot Strategies with Diverse Maps and Enhanced Goal–Targeting Mechanisms - Szpakowska Aleksandra; Artiemjew Piotr; Cybowski Wojciech (International Journal of Applied Mathematics and Computer Science)
Path planning is one of the most important problems in mobile robotics. Particularly challenging in selecting an appropriate path planning method is the choice of a method for complex obstacle configurations. The problems of path planning, among many other methods, come into play with approaches based on the application of potential fields methodology based on physical anomalies with gravitational or electromagnetic fields. This idea makes it possible to navigate in complex maps. The idea of applying these fields in terms of rough mereology was developed by Polkowski and Ośmialowski (2008), who introduced the method of the mereological potential field in the framework of mereological spatial reasoning. This particular work is one of a series of extensions of this method where our final goal is to apply the idea of path planning in a 3D environment. To this end, we are preparing and testing our own library for controlling mobile robots, improving the real-time path planning capability and implementing a set of algorithms for practical testing.